P1 coding region diversity of group vii (sind-08) serotype asia-1 foot-and-mouth disease virus - Waqas ALI; Mudasser HABIB; Rai Shafqat Ali KHAN; Muhammad Ashir ZIA; Muhammad Usman MAZHAR; Asad JAVED; Muhammad FAROOQ; Muhammad Salah Ud Din SHAH (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2018)
In this study, the capsid protein coding region of serotype Asia-1 viruses (n=131) were analyzed, giving importance to the viruses circulating since 2011 within the Group VII (Sind-08). The isolates recovered during 2011-2017 were found to group within the re-emerging cluster of Group VII (Sind-08). The time of the most recent common ancestor for this cluster was estimated to be approximately 2004. In comparison to the older isolates of Group VII (2001-2004), the re-emerging viruses showed variation at fourteen amino acid positions, including substitutions at the antigenically critical residues VP1140, VP1142 and VP277. In Group VII (Sind-08), all three major antigenic sites have mutations (Site I and II had four consensus changes at positions 140, 141 and 77, 79 respectively, while site IV had a replacement at position 59) relative to the internationally recommended vaccine strain (Shamir 89). This study also explains the development and optimization of a new RT-PCR method that may be employed to amplify and sequence a 2901 base pair (bp) section covering entire capsid coding region (P1) of the FMDV genome. This method offers a tool that can be employed for antigenic profiling and phylogenetic analyses of FMDV to help vaccine matching or strain selection in the episode of outbreaks.